A New Approach to Predict the Fundamental Period of Vibration for Newly-designed Reinforced Concrete Buildings. Issue 13 (3rd October 2022) - Ruggieri, Sergio; Fiore, Andrea; Uva, Giuseppina
ABSTRACT: Fundamental period of vibration is one of the most critical parameters to evaluate in the seismic design of new buildings, considering its role in the seismic forces estimation. The challenge of this research is to define a new approach for predicting the fundamental period of vibration for reinforced concrete buildings, designed according to the new generation seismic codes. The proposed formulations in this paper represent useful tools in the pre-design phase and they are based on some global parameters including mass and stiffness properties. To this scope, a set of 40 new buildings have been collected and modelled, considering bare and infilled frame configurations. Through regression analysis procedures two new formulations have been firstly proposed, compared with other existing formulations and finally validated through some case studies proposed in the recent scientific literature. The results show a good agreement with some of the existing formulations and a nearly perfect prediction of the fundamental period of vibration for the selected case study buildings.